Konsepsi dan Pengaturan Kedaulatan Wilayah Udara Indonesia Dalam Aspek Hukum Nasional dan Internasional (Studi Kasus Pesawat Sipil Tanpa Izin dan Pesawat Tempur di Wilayah Zona Ekonomi Eksklusif Indonesia) - Muliawan, Chandra; Gayatri, Syofia; Rianda, Hendi Gusta (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
ABSTRACT:This study aims to analyze the conceptions and regulations of national and international law regarding the sovereignty of airspace in Indonesia which several times threatens Indonesia's sovereignty internationally. The incident analyzed was a civil aircraft flight without a permit on October 22, 2014 and was outside the Indonesian Archipelago Sea Route in the Sulawesi area, then there was also a fighter plane thought to belong to the United States which carried out a maneuver in the Indonesian Exclusive Economic Zone on April 6, 2021 in west of the Natuna Islands. Research in this writing uses a normative juridical research method with a statutory approach (statute aptoach) which is then presented descriptively-analytically. The results of the analysis obtained are first, there is disharmony of laws and regulations related to action in airspace violations committed by foreign aircraft without permission between the Indonesian National Air Force and the Ministry of Transportation, and the non-aplication of sanctions as mandated by Law Number 1 of 2009 concerning Aviation and Government Regulation Number 14 of 2018 concerning Safeguarding the Airspace of the Republic of Indonesia, causing disparities in budgeting and implementation in maintaining territorial sovereignty in the air, secondly, theabsence of both national and international legal instruments that prohibit combat aircraft activities or military activities carried out by a countries in the territory of the Indonesian Exclusive Economic Zone, so the need for the government to issue policies in the form of regulations regarding the Indonesian Exclusive Economic Zone so that there is a ban on military activities in the Indonesian Exclusive Economic Zone, both in regions of Indonesia. water or air.Keywords: Conception, Regulation, Air Sovereignty, IndonesiaABSTRAK:Penelitian ini bertujuan untuk menganalisis mengenai konsepsi dan peraturan hukum nasional maupun internasional mengenai kedaulatan wilayah udara di Indonesia yang beberapa kali mengancam kedaulatan Indonesia secara Internasional. Peristiwa yang dianalisis adalah penerbangan pesawat sipil tanpa izin pada 22 Oktober 2014 dan berada di luar jalur Alur Laut Kepulauan Indonesia (ALKI) di daerah Sulawesi, kemudian ada pula pesawat tempur yang di duga milik Amerika Serikat yang melakukan manuver di Zona Ekonomi Ekslusif Indonesia pada 6 April 2021 di sebelah barat Kepulauan Natuna. Penelitian dalam penulisan ini menggunakan metode penelitian secara yuridis normatif dengan pendekatan peraturan perundang-undangan (statute aptoach) yang kemudian disajikan secara deskriptif-analitis. Hasil analisis yang didapat adalah pertama, adanya disharmoniasi peraturan perundang-undangan terkait penindakan dalam pelanggaran wilayah udara yang dilakukan oleh pesawat asing tanpa izin antara TNI AU dan Kementrian Perhubungan, serta tidak dijalankannya sanksi yang merupakan amanat UU Penerbangan dan PP Pamwilub sehingga menyebabkan disparitas penganggaran dan pelaksanaan dalam menjaga kedaulatan wilayah di udara, kedua,tidak adanya instrumen hukum baik nasional maupun internasional yang melarang aktifitas pesawat tempur maupun aktifitas militer yang dilakukan oleh suatu negara di wiliayah Zona Ekonomi Ekslusif Indonesia, sehingga perlunya pemerintah mengeluarkan kebijakan berupa pengaturan tentang ZEE Indonesia agar adanya larangan aktifitas militer di wilayah ZEE Indonesia baik di daerah perairannya maupun udara.Kata Kunci: Konsepsi, Pengaturan, Kedaulatan Udara, Indonesia